North-South Partnership in God's Mission: Joining Hands in the Construction of a Reconciliation Politics. (October 2022) - Padilla DeBorst, Ruth
This paper asks if there any hope today, in the midst of the pulls and tugs of current globalizing and counter-globalizing forces, of differing theological outlooks and intestine tensions, that the world Church can constitute a politics of reconciliation instead of one characterized by polarized confrontation. Employing the metaphor of "hands, " it proposes some needed steps towards the realization of that hope. Hands can join in reconciliation when they are open in confession and emptied of the manipulation of money, when all hands are welcome at the table, wounded as they are, and when they are raised in communal praise and supplication.